Antifungal Activity of Linear and Disulfide-Cyclized Ultrashort Cationic Lipopeptides Alone and in Combination with Fluconazole against Vulvovaginal Candida spp. - Paulina Czechowicz; Damian Neubauer; Joanna Nowicka; Wojciech Kamysz; Grażyna Gościniak (MDPI AG, 2021)
Vulvovaginal candidiasis (VVC) occurs in over 75% of women at least once during their lifetime and is an infection that significantly affects their health. Candida strains resistant to standard azole antifungal therapy and relapses of VVC are more and more common. Hypothetically, biofilm is one of the main reasons of relapses and failure of the therapy. Ultrashort cationic lipopeptides (USCLs) exhibit high antimicrobial activities. Our previous study on USCLs revealed that disulfide cyclization can result in selective antifungal compounds. Therefore, four USCL were selected and their antifungal activity were studied on 62 clinical strains isolated from VVC. The results confirmed previous premises that cyclic analogs have increased selectivity between fungal cells and keratinocytes and improved anticandidal activity compared to their linear analogs against both planktonic and biofilm cultures. On the other hand, linear lipopeptides in combination with fluconazole showed a synergistic effect. It was found that the minimum inhibitory concentrations of the tested compounds in combination with fluconazole were at least four times lower than when used separately. Our results indicate that combination therapy of VVC with USCLs and fluconazole at low non-toxic concentrations can be beneficial owing to the synergistic effect. However, further in vivo studies are needed to confirm this hypothesis.